Intra Rack Traffic Communication and Peers aware Placement Algorithm for Cloud Data Centers - Tahir, Nuha M.Elhassan; Elballa, Fatima Abdelhalim (2019 International Conference on Computer, Control, Electrical, and Electronics Engineering (ICCCEEE), 2019)
Clouds composed of a collection of resources but in a virtual form which can be provisioned on demand and depending on the cloud customer's needs. Cloud computing customers are in continuous increase which leads to massive resources demand. The process of resource placement efficiently has become a critical problem to be solved in the cloud data center to satisfy the cloud customers demand with low cost for the cloud provider. Over the last eight years, the placement of the virtual machines in cloud environment was a major research subject. Different algorithms have been proposed to achieve the optimal placement results. The majority of these algorithms focused on the optimization based on the CPU and memory as resources, while not giving considerable attention to the network. Few algorithms considered the network communication in the data center but most of them were mono objective. This paper represents a joint objective network communication aware VM placement algorithm, which aims to reduce the intra traffic communication in the cloud data center. This algorithm called Intra Rack Traffic Communication and Peers aware algorithm (IRTCP). The IRTCP has proved better results compared to the common algorithms and the initial placement.